Immune response of oral cholera vaccine, Shanchol in Bangladeshi recipients - Jahan, Sultana Rownok (BRAC University, 2014)
This thesis report is submitted in partial fulfillment of the requirement for the degree of Masters of Science in Biotechnology, 2014.